Implementasi Strategi Pemasaran Pendidikan Melalui Kegiatan Ekstrakulikuler Di MA Raden Rahmat Selorejo Mojowarno Jombang - Zahrotun Ni’mah Afif; Dian Febriansah (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2023)
This research aims to describe the Implementation of a Marketing Strategy Through Extracurricular Activities which is motivated by marketing carried out to overcome competition between educational institutions. Because marketing is very influential on the number of students, with good and structured marketing management, the number of students will increase. This research is intended to answer the following problems: 1) What are the extracurricular activities at MA Raden Rahmat Mojowarno Jombang? 2) How is the implementation of the educational marketing strategy through extracurricular activities at MA Raden Rahmat Mojowarno Jombang? These problems were discussed through research conducted at MA Raden Rahmat Selorejo Mojwarno Jombang where this school was used as a source of data information to obtain portraits, descriptions, answers, and results from the Implementation of Education Marketing Strategies Through Extracurricular Activities. This study uses qualitative research while data collection techniques using methods, interviews, observation, and documentation. All data will be analyzed descriptively, namely by pouring the results into sentences that are arranged in such a way that they can become sentences that are neatly arranged. The results of the research show that: 1) extracurricular activities at MA Raden Rahmat Mojowarno Jombang are sufficient, so these extracurricular activities can be used as capital to compete with other schools. 2) The implementation of the education marketing strategy through extracurricular activities at MA Raden Rahmat Mojowarno Jombang has been going well from planning to evaluating extracurricular activities